Sufi Approaches to Education: The Epistemology of Imam Al-Ghazali - Muhammad Yusuf Fadhil; Saliha Sebgag (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The goal of this paper is to explore the sufi pedagogy that aims to inculcate devout worship and happiness amongst students. Methodologically, this research is qualitative in nature and focuses on the literature of Imam Al-Ghazali. After the data has been collected, the material results are presented systematically with an epistemological analysis. The conclusions of this paper are as follows: ontologically speaking, science is not an abstraction of the object being observed, but the essence of knowledge is a divine light that radiates to the soul (al-ruh ilahiyah) that exists in all humans. Epistemologically, knowledge can be obtained through the optimization of reason. Hence, the mujahadah and the riyadhah are tasks that must be undertaken by students in order to secure the knowledge of mukasyafah. In terms of axiology, knowledge is a means to get closer to Allah, to gain happiness in the world and the hereafter. That is why the profile of the learning outcome of sufi education is ulama' akhirat; namely scholars who have the following characteristics; ‘abid, zahid, ‘alim, faqih and mukhlish.